Effects of Etonogestrel implants on pelvic pain and menstrual flow in women suffering from adenomyosis or endometriosis: Results from a prospective, observational study. Issue 6 (12th February 2021) - Niu, Xiaocen; Luo, Qun; Wang, Chunfen; Zhu, Lihua; Huang, Lili
Abstract : Abstract: Adenomyosis and endometriosis are common causes of pelvic pain in women of reproductive age. Furthermore, adenomyosis is a major cause of menorrhagia. This study aimed to evaluate the effects of Etonogestrel implants on pelvic pain and menstrual flow in women requiring long-acting reversible contraception and suffering from adenomyosis or endometriosis. One hundred women with adenomyosis or endometriosis and asking for contraception with Etonogestrel implants were enrolled in this study and were followed-up for 24 months. Patients were interviewed on pelvic pain by visual analog scale (VAS) pain score, menstrual flow by the number of sanitary napkins, menstrual bleeding pattern, weight gain, breast pain, and any other treatment side effects. Seventy four patients who were treated with Etonogestrel implants completed the 24-month follow-up in which we found a significant decrease in pelvic pain VAS scores comparing baseline scores to 6, 12, and 24 months (baseline: 6.39 ± 2.35 to 24-month: 0.17 ± 0.69, P < 0.05). The menstrual volume decreased significantly compared with that at baseline ((40.69 ± 30.92) %, P < 0.05). However, vaginal bleeding, amenorrhea, weight gain, and acne occurred after treatment in some patients. Etonogestrel implants were effective in reducing pelvic pain and menstrual flow of adenomyosis or endometriosis.